An Islamic Perspective on Coping with Life Stressors - Achour, M.; Bensaid, B.; Nor, M.R.M. (Springer Verlag (Germany), 2016)
There is growing popularity among researchers, human-resource managers, and policy makers concerning the efficacy of coping strategies on employee well-being and work-family conflict. The role of religious belief and spiritual support mechanisms in maintaining effective well-being remains understudied. This research explores the Islamic concept and categories of coping strategies, and discusses the role they play in promoting the well-being of Muslim employees in general. We further examine various religious strategies that Muslims often use to cope with life stressors including religiosity, belief, trust in God, prayer, forbearance, supplication, recitation of the Qur’an, remembrance of God, patience and thankfulness; all of which serve as effective coping strategies and mechanisms in the face of life stressors.